The Role of Arbuscular Mycorrhiza Fungi in the Decomposition of Fresh Residue and Soil Organic Carbon: A Mini‐Review. Issue 3 (1st May 2019) - Wei, Lili; Vosátka, Miroslav; Cai, Bangping; Ding, Jing; Lu, Changyi; Xu, Jinghua; Yan, Wenfei; Li, Yuhong; Liu, Chaoxiang
Abstract : Core Ideas: Our discussion highlights the role of arbuscular mycorrhizal fungi in organic decomposition processes. Arbuscular mycorrhizal fungi can stimulate fresh residue decomposition initially and then tend to suppress the decomposition of old or decomposed soil organic carbon. We offer implication that arbuscular mycorrhizal fungi would benefit soil carbon gain in the long term even under elevated atmospheric carbon dioxide. Arbuscular mycorrhizal fungi (AMF) are widespread in terrestrial ecosystems. In addition to their contributions to plant nutrient uptake, AMF also provide many ecological functions including regulation of soil C dynamics. However, both stimulating and retarding soil organic decomposition by AMF have been observed. Here we discuss the possible reasons for such a contradiction. Arbuscular mycorrhizal fungi contribute to soil aggregation mainly through hyphal enmeshment, saprotrophic suppression, and production of glomalin‐related soil proteins, while AMF can also stimulate organic decomposition through promoting degradative enzymes, modifying root production and activity, and/or through regulating the microbial community in the mycorrhizosphere and hyphosphere. The role of AMF in C decomposition is strongly dependent on the quality and quantity of different soil C pools. Arbuscular mycorrhizal fungi can stimulate fresh residue decomposition initially through stimulating the decomposition of fresh residues (particularly those having high C/N ratio), whereas for older or decomposed soil organic C, AMF tend to suppress decomposition by promoting soil aggregation. Under elevated CO2 (eCO2 ), AMF show additive effects on residue decomposition, priming effects, and changes in soil aggregation. Despite organic decomposition rates differing in the short term and long term following litter experiments, our discussion highlights the role of AMF in organic C dynamics. We hypothesize that AMF would benefit soil C gain in the long term and thereby predict that disturbances that impacts negatively on AMF, such as tillage, residue burning, fertilization, and fungicide application, would lead to soil C decline particularly under eCO2 .